(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to develop a proposed program for auditing deferred regulatory accounts in accordance with international auditing standards to address the challenges faced by auditors in examining these accounts and ensuring compliance with financial disclosure and transparency requirements. The importance of the research is manifested in the need for a unified audit framework that enhances the accuracy of measurement and disclosure of deferred regulatory accounts, which contributes to improving the quality of financial reporting and the reliability of information provided to stakeholders. The research adopts a descriptive and analytical approach, analyzing the relevant international standards and examining the audit practices followed, in addition to proposing an audit program that can be applied in organizations to effectively audit these accounts. The research concluded that applying the proposed program would improve the audit process, reduce accounting errors and risks, and enhance the credibility of the financial statements.